2021
DOI: 10.1073/pnas.2015080118
|View full text |Cite
|
Sign up to set email alerts
|

Natural resistance to worms exacerbates bovine tuberculosis severity independently of worm coinfection

Abstract: Pathogen interactions arising during coinfection can exacerbate disease severity, for example when the immune response mounted against one pathogen negatively affects defense of another. It is also possible that host immune responses to a pathogen, shaped by historical evolutionary interactions between host and pathogen, may modify host immune defenses in ways that have repercussions for other pathogens. In this case, negative interactions between two pathogens could emerge even in the absence of concurrent in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Although believed to be poorly phagocytic, many MGCs in bovine tuberculoid granulomas contain one to several AFB (Figure 4) [56]. In cattle and other ruminants, the number of MGCs has been used as a measure of lesion severity, with higher numbers of MGCs associated with greater antigen persistence, increased inflammation, and more severe disease [35,64].…”
Section: Epithelioid Macrophages Foamy Macrophages and Multinucleated...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although believed to be poorly phagocytic, many MGCs in bovine tuberculoid granulomas contain one to several AFB (Figure 4) [56]. In cattle and other ruminants, the number of MGCs has been used as a measure of lesion severity, with higher numbers of MGCs associated with greater antigen persistence, increased inflammation, and more severe disease [35,64].…”
Section: Epithelioid Macrophages Foamy Macrophages and Multinucleated...mentioning
confidence: 99%
“…As granulomas progress from stages I-IV an initial collection of CD68 + macrophages and CD68 + MGCs becomes a mixture of macrophages, MGCs and lymphocytes In cattle and other ruminants, the number of MGCs has been used as a measure of lesion severity, with higher numbers of MGCs associated with greater antigen persistence, increased inflammation, and more severe disease [35,64].…”
Section: Lymphocyte Responsementioning
confidence: 99%
“…There were 9 uninfected and 22 coccidia-infected individuals. Following the methods of Ezenwa et al ( 2021 ), we used a model-based approach to identify statistically significant clusters in the oocyst intensity data (S3) using the mclust package (Fraley et al 2021 ). We then classified infected individuals into two groups based on these clusters [Low (< 100 oocysts per gram feces (opg)): n = 11; High (> 100 opg): n = 10].…”
Section: Methodsmentioning
confidence: 99%
“…and gastrointestinal nematodes ( Aspicularis americana (a pinworm) and 3 stryongylid (hookworm) species) (Uninfected: n = 9; Low coccidia (< 100 opg): n = 9; High coccidia (> 100 opg): n = 7; Coinfected: n = 5; Table S2). Due to their similar biology and the general suite of host immune responses they trigger, grouping all gastrointestinal nematodes together for analysis is common for genetic studies of host resistance (Oppelt et al 2010 ; Brambilla et al 2015 ; Portanier et al 2019 ; Ezenwa et al 2021 ; Ahbara et al 2021 ) as well as coccidia-nematode coinfection studies (Knowles et al 2013 ; Pedersen and Antonovics 2013 ; Gorsich et al 2014 ; Yan et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Key findings from this study population have largely focused on understanding the interplay between intestinal nematode infections and BTB. For example, a study of 209 initially BTB negative adult female buffalo tracked over a four-year period demonstrated that animals with greater natural resistance to worms based on strongyle parasite faecal egg counts (FEC) were more likely to die from BTB than non-resistant individuals, and that BTB disease progression was more rapid in worm resistant individuals [ 100 ]. The authors demonstrated in a subset of animals that the worm resistant phenotype was associated with increased mucosal mast cells, eosinophils and IgA in the abomasum (gastric stomach) and small intestine, the primary sites of infection by strongyle parasites, which is consistent with a more pronounced Type 2 immune response in resistant individuals.…”
Section: Introducing Wild Ungulate Study Systemsmentioning
confidence: 99%